2015
DOI: 10.1097/icu.0000000000000130
|View full text |Cite
|
Sign up to set email alerts
|

Corneal hysteresis and its relevance to glaucoma

Abstract: Purpose of reviewGlaucoma is a leading cause of irreversible blindness worldwide. It is estimated that roughly 60.5 million people had glaucoma in 2010 and that this number is increasing. Many patients continue to lose vision despite apparent disease control according to traditional risk factors. The purpose of this review is to discuss the recent findings with regard to corneal hysteresis, a variable that is thought to be associated with the risk and progression of glaucoma.Recent findingsLow corneal hysteres… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
85
1
4

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 108 publications
(93 citation statements)
references
References 53 publications
3
85
1
4
Order By: Relevance
“…cornea and lamina thickness) (Jonas and Holbach, 2005), or with susceptibility to disease (cornea thickness and hysteresis vs. glaucoma progression) (Deol et al, 2015; Medeiros et al, 2013). We have demonstrated that we can detect not only the front and back of the eye simultaneously, but the side as well.…”
Section: Discussionmentioning
confidence: 99%
“…cornea and lamina thickness) (Jonas and Holbach, 2005), or with susceptibility to disease (cornea thickness and hysteresis vs. glaucoma progression) (Deol et al, 2015; Medeiros et al, 2013). We have demonstrated that we can detect not only the front and back of the eye simultaneously, but the side as well.…”
Section: Discussionmentioning
confidence: 99%
“…CCT is reportedly thinner in people of African ancestry (Chua et al, 2014; Sample et al, 2009). Although the mechanism is unclear, thinner CCT has been reported as a strong predictor of POAG risk (Deol et al, 2015; Gordon et al, 2002; Sng et al, 2017). Thicker CCT is associated with ocular hypertension and glaucoma suspect status in adults and children (Gordon et al, 2002; Muir et al, 2004).…”
Section: Genetic Analyses Of Poag-associated Traits (Endophenotypes)mentioning
confidence: 99%
“…5 Keratoconus, Fuchs' dystrophy, Glaucoma, Marfan syndrome, and post-LASIK patients have been found to have low CH and CRF. [6][7][8][9][10][11][12][13] The corneal visualization Scheimpflug technology tonometer (Corvis ST tonometry: CST; Oculus, Wetzlar, Germany) was introduced more recently and allows quantitative and visual assessment of the biomechanical properties of the cornea. 14 The Corvis ST is a noncontact tonometer with an integrated ultra-high-speed Scheimpflug camera, enabling the direct visualization of corneal movement during the application of a rapid air-puff.…”
Section: Clinical Evaluation Of the Biomechanical Changes Occurring Imentioning
confidence: 99%